2017
DOI: 10.4172/2161-0932.s5:06
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Ovarian Cancer with Transvaginal Microbubble Sonography: Current and Potential Applications

Abstract: Contrast Enhanced microbubble Transvaginal Sonography (CE-TVS) can distinguish benign and malignant ovarian tumors. Initial results from several medical centers around the world have indicated that there are unique enhancement patterns in ovarian neoplasms. Challenges to the implementation of CE-TVS remain since some aggressive ovarian tumors (type 2) that arise in the tubal epithelium and metastasize without producing a clinically detectable mass may be difficult to detect. This is being addressed through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…(25) RESEARCH AND FUTURE POSSIBILITIES Development of technology in future and introduction of "3D quantification of blood flow" called "the 3D colour histogram," may improve differentiation between benign and malignant ovarian tumors. (26)(27)(28) Microbubble enhanced transvaginal sonography is also being tried to improve the diagnosis of malignant masses by early detection of tumour microvascularity. Using microbubbles that are small enough to pass through capillaries, the kinetics of the blood flow can be analysed to detect abnormal flow found in areas of neovascularisation.…”
Section: Discussionmentioning
confidence: 99%
“…(25) RESEARCH AND FUTURE POSSIBILITIES Development of technology in future and introduction of "3D quantification of blood flow" called "the 3D colour histogram," may improve differentiation between benign and malignant ovarian tumors. (26)(27)(28) Microbubble enhanced transvaginal sonography is also being tried to improve the diagnosis of malignant masses by early detection of tumour microvascularity. Using microbubbles that are small enough to pass through capillaries, the kinetics of the blood flow can be analysed to detect abnormal flow found in areas of neovascularisation.…”
Section: Discussionmentioning
confidence: 99%
“…Microbubbles are also being used in pediatric patients who receive blunt trauma with imaging of the kidneys, spleen, liver and pancreas. Initial studies have demonstrated significant differences in vascular enhancements of benign versus malignant masses [1][2][3]. Although contrast-enhanced transvaginal sonography cannot distinguish between borderline and malignant masses, both require surgical intervention [3].…”
Section: Success Thus Farmentioning
confidence: 99%
“…However early detection can potentially improve the survival rate from 50 to 90%. Transvaginal sonography with the use of contrast-enhanced microbubbles has shown promise when used to detect malignant ovarian lesions in several studies [1][2][3]. This brief communication addresses the need and potential benefits of contrast enhanced transvaginal sonography, as well as directions for future research and clinical applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations